2012
DOI: 10.1186/1471-2164-13-445
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of the operon encoding stress-responsive ECF sigma factor SigH and its anti-sigma factor RshA, and control of its regulatory network in Corynebacterium glutamicum

Abstract: BackgroundThe expression of genes in Corynebacterium glutamicum, a Gram-positive non-pathogenic bacterium used mainly for the industrial production of amino acids, is regulated by seven different sigma factors of RNA polymerase, including the stress-responsive ECF-sigma factor SigH. The sigH gene is located in a gene cluster together with the rshA gene, putatively encoding an anti-sigma factor. The aim of this study was to analyze the transcriptional regulation of the sigH and rshA gene cluster and the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
108
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 73 publications
(120 citation statements)
references
References 58 publications
(120 reference statements)
10
108
1
Order By: Relevance
“…Although no such ORF has been annotated in the genome of C. glutamicum R (42), which was used as the wild-type strain in this study (see Table S1 in the supplemental material), reinspection of the genome revealed a small (267-bp) ORF (cgR_6064) encoding a protein with 100% amino acid sequence identity with the anti-factor RshA, as has been reported previously (25). As H is constitutively active in the rshA mutant, expression of the H regulon is upregulated in the absence of any stress (25). We confirmed that the expression level of mtr (cgR_1832), one of the components of the H regulon in C. glutamicum R (14), was upregulated more than 10-fold by deletion of the rshA gene during normal growth (data not shown).…”
Section: Resultssupporting
confidence: 54%
See 4 more Smart Citations
“…Although no such ORF has been annotated in the genome of C. glutamicum R (42), which was used as the wild-type strain in this study (see Table S1 in the supplemental material), reinspection of the genome revealed a small (267-bp) ORF (cgR_6064) encoding a protein with 100% amino acid sequence identity with the anti-factor RshA, as has been reported previously (25). As H is constitutively active in the rshA mutant, expression of the H regulon is upregulated in the absence of any stress (25). We confirmed that the expression level of mtr (cgR_1832), one of the components of the H regulon in C. glutamicum R (14), was upregulated more than 10-fold by deletion of the rshA gene during normal growth (data not shown).…”
Section: Resultssupporting
confidence: 54%
“…In total, 74 genes were found upregulated 2-fold or more in the rshA deletion mutant compared to the level of the wild type. Among them, 34 genes have been previously shown to be upregulated by overexpression of H or deletion of rshA under normal growth conditions (14,25). These results not only confirmed that RshA is the anti-H but also showed that there are H regulon genes yet to be identified.…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations